Microgreen leaf vegetable production by different wavelengths - Kovácsné Madar, Ágota; Vargas-Rubóczki, Tímea; Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2022)
Microgreens are becoming more popular in gastronomy, especially as a salad ingredient. In this study, two plant species belonging to the cabbage family were grown as microgreens, namely red cabbage and broccoli. Three different light-emitting diodes (LEDs) were used in the experiment, blue, red, and combined (blue:red) lighting. The experiment was carried out by 118 µmol-2 s-1total Photosynthetic Photon Flux (PPF), LED lighting was applied for 16 hours a day. Blue light primarily stimulates leaf growth, while red light promotes flowering. In our experiment, blue and combined lighting favorably affected plant development, yield (~3000 g m-2), chlorophyll-a (~8.0 mg g-1), and carotenoid content (9.0 mg g-1). However, the red light resulted in reduced harvest yields (~2200 g m-2), chlorophyll-a (~6.0 mg g-1), and carotenoid content (~7.0 mg g-1). The development of red cabbage was favorably influenced by the blue spectrum, while the combined spectrum favorably influenced the development of broccoli.